Explaining the formation of eudaimonic gaming experiences: a theoretical overview and systemization based on interactivity and game elements - Possler, Daniel; Bowman, Nicholas David; Daneels, Rowan (Frontiers in Communication, 2023)
Over the past years, scholars have explored eudaimonic video game experiences—profound entertainment responses that include meaningfulness, reflection, and others. In a comparatively short time, a plethora of explanations for the formation of such eudaimonic gaming experiences has been developed across multiple disciplines, making it difficult to keep track of the state of theory development. Hence, we present a theoretical overview of these explanations. We first provide a working definition of eudaimonic gaming experiences (i.e., experiences that reflect human virtues and encourage players to develop their potential as human beings fully) and outline four layers of video games—agency, narrative, sociality, and aesthetics—that form the basis for theorizing. Subsequently, we provide an overview of the theoretical approaches, categorizing them based on which of the four game layers their explanation mainly rests upon. Finally, we suggest the contingency of the different theoretical approaches for explaining eudaimonic experiences by describing how their usefulness varies as a function of interactivity. As different types of games offer players various levels of interactivity, our overview suggests which theories and which game layers should be considered when examining eudaimonic experiences for specific game types.